Electrical Energy Storage by a Magnesium-Copper-Sulfide Rechargeable Battery. Issue 4 (1st January 2017) - Thiele, Philipp; Neumann, Johannes; Westphal, Anne; Ludwig, Ralf; Bonsa, Anne-Marie; Appelhagen, Andreas; Malcher, Peter; Köckerling, Martin
Abstract : A novel battery system consisting of Mg/MgS and Cu/CuS electrodes and a novel anion conductor has been developed. The sulfide based electrolyte contains Li2 S and Li-TFSI in triglyme. After the first cycle it shows cycle stability for 10 measured cycles, and a high initial capacity of ∼660 mAh⋅g −1 (based on the mass of magnesium), which drops to ∼100 mAh⋅g −1 after the first cycle. Cu/CuS and Mg/MgS electrodes as well as full cells from these electrodes were developed and tested. Experimental and theoretical work was conducted with special focus on the electrolyte. Solutions of various inorganic and organic sulfides were tested for high concentration, (electro-)chemical stability, viscosity and ionic conductivity. Good results were obtained for a solution of Li2 S and Li-TFSI (Lithium-bis(trifluoromethane)sulfonimide) in triglyme. Raman investigations prove that CuS forms and disappears reversibly on the electrode surfaces, i.e. that it is in fact a battery with anion conductor.